The Cardiorespiratory Fitness of Children and the Anthropometric Determinants During Late Childhood Within South East Wales: Potential Implications for Future Health - Stuart Jarvis PhD; Helen Giles PhD; Karl J. New PhD (SAGE Publishing, 2024)
Objective. This study investigated cardiorespiratory fitness (CRF) levels and the relationship with field-based measures of anthropometry in children aged 10 to 11 years. Methods . A total of 288 boys and 257 girls participated in the study. CRF (20 m shuttle run) and several field-based measures of anthropometry were assessed. Multiple regression was utilized for all data analysis. Results. Boys performed significantly better than girls on the CRF test ( P  < .001) and achieved higher classifications of CRF based on centile norms compared to girls. All measures of anthropometry were significant predictors of CRF, ( P  < .001), and each measure was significant in predicting a negative trajectory of CRF performance when they increased in value ( P  < .05). Conclusion . The study findings add to the international reporting of CRF and the use of simple field-based measures of anthropometry alongside the use of BMI to predict CRF for health with Welsh school children (UK).